Perkembangan Sosial dan Emosional pada Anak Sekolah Dasar - Gultom, Lois Enjelina; Berlianti, Berlianti; Ritonga, Fajar Utama (Medan Resource Center, 2023)
Teaching Campus is a learning channel that provides opportunities for students to study off- campus for one semester to practice their ability to solve complex problems by becoming partners with teachers to innovate in learning, develop strategies and learning models that are creative, innovative and fun. Campus Policy Merdeka Learning aims to encourage students to master various fields of knowledge with their areas of expertise, so that they are ready to compete in the global world. Social Emotional Learning is closely related to the philosophy of thought 'Ki Hajar Dewantara' which states that the purpose of education is to guide all the strengths or natures that exist in children so that they can achieve the highest possible safety and happiness, and here I and we or the teacher's role is a driving force as an example of character education for students, creating an educational ecosystem, and organizing a learning environment that is full of comfort, safety and fun. That way positive emotions and moods will be created in children, and we can know them.